Proposing Electric Motorcycle Adoption-Diffusion Model in Indonesia: A System Dynamics Approach - Dwi Setyo Sulistyono; Yuniaristanto; Wahyudi Sutopo; Muhammad Hisjam (Jurnal Optimasi Sistem Industri, 2021)
In 2019, the number of conventional vehicles in Indonesia reached 133,617,012 units, dominated by motorcycles of 112,771,136 units and passenger cars of 15,592,419 units. The high number of conventional motorcycle users can increase the number of pollutants and combustion emissions in the environment. This condition has encouraged the transition to a sustainable transport system that will be needed for decades to come, especially for the electric motorcycle to resolve the issue. This research aims to predict and estimate the market share of electric motorcycles by considering life cycle cost per kilometer. System dynamics simulations are developed to model the adoption-diffusion of electric motorcycles in Indonesia. This model has four main modules: an electric motorcycle module, a conventional motorcycle module, an economy module, and a consumer market module. This model shows a positive trend of EM market share from 2021-2030, with the market share value of EM is 0,411 in 2030. The development of retail price subsidy and electricity price scenarios is also carried out to determine the right policies to accelerate the adoption-diffusion process. Based on the scenario, the provision of retail price subsidy and a decrease in electricity price can increase the value of the EM Market Share.